2015
DOI: 10.1039/c5nj00344j
|View full text |Cite|
|
Sign up to set email alerts
|

Pd complex of an NNN pincer ligand supported on γ-Fe2O3@SiO2 magnetic nanoparticles: a new catalyst for Heck, Suzuki and Sonogashira coupling reactions

Abstract: Pd-BIP-γ-Fe2O3@SiO2 was used successfully as an air- and moisture-stable magnetically recyclable catalyst for Heck, Suzuki and Sonogashira coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…PXRD patterns and SEM images were consistent with reported data. [144]). The pilot reaction used for catalytic studies was the Claisen-Schmidt condensation of benzaldehyde with acetophenone.…”
Section: Scheme37 Suzuki-miyaura Coupling Using Irmof-3-pi-pd [137a]mentioning
confidence: 99%
“…PXRD patterns and SEM images were consistent with reported data. [144]). The pilot reaction used for catalytic studies was the Claisen-Schmidt condensation of benzaldehyde with acetophenone.…”
Section: Scheme37 Suzuki-miyaura Coupling Using Irmof-3-pi-pd [137a]mentioning
confidence: 99%
“…As mentiomed in leterature, in the case of noble metals, one of the most widely used methods to stabilize the nanoparticles and control their growth is to use ligands and it is observed that tridentate nitrogen ligands, including terpyridine‐based ligands, increase the dispersion and stability of the metal nanoparticles due to the strong interaction metal‐nitrogen and the formation of two five‐membered metallacycles …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the pyridine maghemite coated-grafted catalyst 62 has been successfully used in the classical Sonogashira reaction with phenylacetylene, the use of chloroarenes needing longer reaction times and reaching lower yields that the related iodoarenes [108]. In addition, another possibility is the stabilization of the palladium by carbine-phospane ligands, as in the case of supported catalyst 63, which allowed to perform the cross-coupling reaction using water as solvent and very low catalyst loading [109].…”
Section: Magnetic Material-supported Palladium Catalystsmentioning
confidence: 99%